Sosialisasi Pengkajian Dampak Ekonomi Semarang Great Sale 2024 Dalam Pemberian Diskon Pajak Kepada Pelaku Usaha - Imang Dapit Pamungkas; Agung Prajanto; Hermawan Triono (Jurnal Pengabdian Masyarakat Waradin, 2024)
Semarang Great Sale (Semargres) is an annual event held by the Semarang City Government and the Semarang City Chamber of Commerce and Industry (KADIN) from 2010 to 2023. This event aims to strengthen relations between Semarang City business actors, including the hotel sector, shopping centers, souvenir producers, retail traders, MSMEs, SMEs, and street vendors. Semargres 2024 will be held from August to early September 2024, with the closing at Queen City Mall Semarang on September 2, 2024. As support, the Semarang City Government and the hotel, restaurant, and entertainment sectors provide a 20% tax break to eligible Semargres participants based on November 2023 taxes and compensated for December 2023 taxes. The Lecturer Team of the Faculty of Economics and Business, Dian Nuswantoro University, implements this community service program in collaboration with KADIN and the Semarang City Government through the Regional Revenue Agency. This program aims to socialize the study of the results of the implementation of Semargres 2024 as a basis for providing tax discounts. This activity is expected to increase the understanding of business actors about the benefits and mechanisms of providing tax discounts, encourage their active participation in Semargres in the future, and be a reference for the development of the local economy of Semarang City.